Fruiting Branch K+ Level Affects Cotton Fiber Elongation Through Osmoregulation - Yang, Jiashuo; Hu, Wei; Zhao, Wenqing; Chen, Binglin; Wang, Youhua; Zhou, Zhiguo; Meng, Yali (Frontiers in Plant Science, 2016)
Potassium (K) deficiency in cotton plants results in reduced fibre length. As one of the primary osmotica, K+ contributes to an increase in cell turgor pressure during fibre elongation. Therefore, it is hypothesized that fibre length is affected by K deficiency through an osmotic pathway, so in 2012 and 2013, an experiment was conducted to test this hypothesis by imposing three potassium supply regimes (0, 125, 250 kg K ha-1) on a low-K-sensitive cultivar, Siza 3, and a low-K-tolerant cultivar, Simian 3. We found that fibres were longer in the later season bolls than in the earlier ones in cotton plants grown under normal growth conditions, but later season bolls showed a greater sensitivity to low-K stress, especially the low-K sensitive genotype. We also found that the maximum velocity of fibre elongation (Vmax) is the parameter that best reflects the change in fibre elongation under K deficiency. This parameter mostly depends on cell turgor, so the content of the osmotically active solutes was analysed accordingly. Statistical analysis showed that K+ was the major osmotic factor affecting fibre length, and malate was likely facilitating K+ accumulation into fibres, which enabled the low-K-tolerant genotype to cope with low-K stress. Moreover, the low-K-tolerant genotype tended to have greater K+ absorptive capacities in the upper fruiting branches. Based on our findings, we suggest a fertilization scheme for Gossypium hirsutum that adds extra potash fertilizer or distributes it during the development of late season bolls to mitigate K deficiency in the second half of the growth season and to enhance fibre length in late season bolls.